Nilai-Nilai Akhlak Sosial dalam Surah Al-Hujurat Ayat 11-13: Studi Komparatif Tafsir Al-Maraghi dan Al-Mishbah serta Relevansinya terhadap Pembinaan Karakter Religius Peserta Didik - Nor Hidayati; Moh. Romli; Herlina Herlina (Pascasarjana IAI Nasional Laa Roiba Bogor, 2026)
This research is motivated by the persistent gap between the ideal of Islamic education in fostering students' social ethics and the reality of behaviors such as bullying and lack of empathy. The author is interested in comparing the interpretations of Al-Maraghi and M. Quraish Shihab on QS. Al-Hujurāt verses 11–13, as comparative studies between the two remain limited. This study employs a qualitative approach using library research method. Data were collected through analysis of Tafsir Al-Marāghī and Tafsir Al-Mishbah, applying thematic (maudhū'ī) and comparative (muqāran) exegetical approaches to examine the social-ethical values in QS. Al-Hujurāt verses 11–13 and their relevance to the religious character development of students. The findings indicate that QS. Al-Hujurāt verses 11–13 contains social-ethical values encompassing human dignity, husnuẓẓan, equality, and taʿaruf. Both exegetes agree on the substantive values while differing in approach: Al-Maraghi is normative-systematic, whereas Al-Mishbah is reflective-contextual. These values are relevant to students' religious character development through the dimensions of honesty, tolerance, and social care.